2013
DOI: 10.1007/s11606-013-2378-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving Efficiency of Clinical Skills Training: A Randomized Trial

Abstract: Dyad training of pre-clerkship medical students' patient encounter skills is effective, efficient, and prompts higher confidence in managing future patient encounters compared to training alone. This training format may help maintain high-quality medical training in the face of an increasing number of students in medical schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 26 publications
4
56
0
Order By: Relevance
“…Finally, we examined only the immediate effects of dyad practice on skills transfer and did not attempt to evaluate effects on skills retention. This has, however, been examined in several recent studies, in which no significant differences were found between dyad and single practice in the simulated setting after delays of 2–3 weeks 15, 16, 17, 36…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Finally, we examined only the immediate effects of dyad practice on skills transfer and did not attempt to evaluate effects on skills retention. This has, however, been examined in several recent studies, in which no significant differences were found between dyad and single practice in the simulated setting after delays of 2–3 weeks 15, 16, 17, 36…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, although dyad practice is as effective as individual practice during simulation‐based training, it does not guarantee equivalent skills transfer. The positive effects of dyad practice on confidence and metacognition reported in previous studies15, 17 indicate that dyad practice may actually improve the chances of successful skills transfer according to social cognitive theory 19, 22. However, the decreased amount of hands‐on experience may reduce dyad participants’ automaticity of skills during simulation‐based practice, which may impair subsequent skills transfer according to the motor skills learning literature 23, 24…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Students in a mental health clerkship, learning adolescent psychopathology through cooperative learning, gained more knowledge of the topic than students who learned through lectures (Bahar-Ozvaris, Cetin, Turan, & Peters, 2006). Other researchers (Tolsgaard, Bjørck, Rasmussen, Gustafsson, & Ringsted, 2013) found that training with another learner improves the effectiveness and efficiency of the training session and has positive effects on a clinician's confidence in managing patient cases. Consistent with the introductory message of this article, clinicians must recognize the effectiveness of cooperation and working in teams.…”
Section: Cooperative-based Learningmentioning
confidence: 99%
“…This study evaluated the effect of dyad versus solo training on patient encounter skills among pre-clerkship medical students. 4 Forty-nine students participated in a 4-hour course on performing histories and physical examinations, and were then randomized to spend a 4-hour practice session with standardized patients (SP) in dyads or alone. Solo students had 25 minutes for the encounter and 25 minutes to develop a write-up for four cases.…”
Section: Resultsmentioning
confidence: 99%